Optimizing Speaking Proficiency in Indonesian EFL Higher Education: A Pedagogical Intervention Using the IELTS Question Framework - Nurul Hasanah; Yessicka Noviasmy; Mutia Fauziatulhaq; Nur Zarimah (Institut Agama Islam Negeri Palopo, 2024)
This study evaluates the effectiveness of a pedagogical intervention using the IELTS Speaking Part question framework to improve speaking skills among students in the English Education Program at IAIN Parepare. The intervention introduced most students to the IELTS Speaking format for the first time, focusing on familiarizing them with speaking techniques that align with international standards. A pre-experimental design was employed, with a one-group pretest-posttest method. The research involved 57 students from the PBI 2022 cohort, with a sample of 15 students (Class PBI4C) selected through cluster purposive sampling. The primary instrument was a speaking test structured around the IELTS framework, with scores measured on a 0-100 scale to allow for detailed interval analysis. Data analysis, conducted in Microsoft Excel, revealed a significant improvement, as the average score rose from 63.7 (pretest) to 83.17 (posttest). A t-test confirmed a statistically significant difference, with a t-value of 5.91 exceeding the t-table value of 2.14 at a 0.05 significance level. These results suggest that using the IELTS-based framework effectively enhanced students’ speaking skills, providing valuable exposure to international testing standards.